Probabilities and Shannon's Entropy in the Everett Many-Worlds Theory - Wichert, Andreas; Moreira, Catarina (Frontiers in Physics, 2016)
Following a controversial suggestion by David Deutsch that decision theory can solve the problem of probabilities in the Everett many-worlds we suggest that the probabilities are induced by Shannon's entropy that measures the uncertainty of events. We argue that a relational person prefers certainty to uncertainty due to fundamental biological principle of homeostasis.